Childhood adversities and 5-HTTLPR polymorphism as risk factors of substance use disorders: retrospective case-control study in Murcia (Spain) - Ronald C Kessler; Jose Maria Huerta; Fernando Navarro-Mateu; Mari Paz Quesada; Teresa Escámez; Mª José Alcaráz; Catherine Seiquer de la Peña; Diego Salmerón; Gemma Vilagut; Maria Dolores Chirlaque; Carmen Navarro; Mathilde Husky; et al. (BMJ Open)
Objective To explore the separate and joint associations of childhood adversities and 5-HTTLPR polymorphism as risk factors for substance use disorders among adults.Design Retrospective case-control study.Setting Cases from the substance unit and controls from a representative sample of the adult general population in the metropolitan area of Murcia (Spain).Participants Cases were defined as outpatients 18 years old or older currently in the treatment for alcohol, opioids or cocaine use disorders in the clinical unit. Controls were randomly selected among individuals without substance use disorders who participated in the Psychiatric Enquiry to General Population in Southeast Spain-Murcia (PEGASUS-Murcia) project, a cross-sectional study of a representative sample of the adult general population. In all, 142 cases and 531 controls were interviewed and a subsample of 114 cases (80.3%) and 329 controls (62%) provided a biological sample.Exposure A history of 12 childhood adversities, lifetime mental disorders and sociodemographic variables was assessed with the Composite International Diagnostic Interview (CIDI)version 3.0). Buccal swabs were obtained to genotype the 5-HTTLPR polymorphism with the biallelic and the triallelic classification.Main outcome and measure Multivariable logistic regression models were performed to estimate adjusted ORs and 95% CI.Results Childhood adversities were associated with an elevated risk of substance use disorders (OR=5.77, 95% CI 3.46 to 9.61). Homozygotes for the short allele of the 5-HTTLPR polymorphism also showed the elevated risk of substance use disorders for the biallelic and triallelic classification: (1.97 (1.10 to 3.55) and 2.01 (1.11 to 3.64), respectively). No evidence for gene × environment interactions was found.Conclusions Childhood adversities and the 5-HTTLPR polymorphism are involved in the aetiology of substance use disorders though findings exploring the existence of a gene–environment interaction were inconclusive.